Effect of Wheat Germ on Quality of Wheat Bread Dough - M. Noori, Lehat Yousif; Sabir, Dler Amin (Kurdistan Journal of Applied Research, 2019)
The most interesting component of wheat is the wheat germ that is recognized as a secondary product in the industry of wheat milling; it has fascinating nutritional values that cannot be ignored. However, it has slender usage due to its significant chance of rancidity and the negative effect it causes the dough quality. Investigation in this study showed that how wheat germ affects the rheological quality of dough and the influences on the final product by its addition to bread, also to find out the best and most amount of wheat germ addition with the best bread quality that is unrecognizable by customers. For this intention, divergent quantities of the mille draw germ of wheat (5%, 10%, 15%, and 20%) were added to the flour used for making bread dough. Afterward, the dough’s rheological characteristics and the endmost quality characteristics of the bread were analyzed and compared to the control sample from both the Sensory evaluation and physical evaluation sentiments. Wheat germ insertion to dough flour caused an increase browning of the dough but decreased dough firmness, stretch-ability, and dough strength. The more the amount of the additional wheat germ to the wheat dough, the more the changes appeared, including decreasing extensibility and strength in addition to taste the difference. The bread made from dough with the highest amount of inserted wheat germ dispensed the smaller volume, less elasticity, and cohesiveness, while more firm and darker in color of both crust and crumb of the product. All bread acquired allowable outcomes in the sensory examination, yet inserting of wheat germ with a rate of (20% to flour) decreased appearance, texture, and overall acceptability outcomes of bread. Consequently, the addition of the germ worsens the rheology attribution of dough, lessen gelatinization temperature and qualification of bread, so it has to be added in a particular amount to keep both nutritional value and the quality of the bread as high as possible.